Marie Darrieussecq’s Clèves: A Wittigian Rewriting of Adolescence - Annabel L Kim (Studies in 20th & 21st Century Literature, 2016)
Marie Darrieussecq's Clèves (2011) shocked readers with the vulgarity of its language and spurred controversy over its status as a literary text. In this article, I show how the novel's "bad" language is a foil for Darrieussecq's larger project of rewriting the adolescent female body, removing it from the sexualized and objectified optic through which it is usually viewed in order to stage it instead as a body in process, as a situation. For this body in process, gender and sexuality are not givens, but deeply unfamiliar experiences that resist the social order’s dominant framing narratives, its scripts for normal and normative subjectivation. The novel, through a Wittigian universalization of the particular point of view of the female adolescent, gives readers access to the experience and the knowledge provided by her body in process.
Keywords: Darrieussecq; Wittig; adolescence; body; sexuality; gender; bad literature; obscenity; Clèves; intertextuality; contemporary literature